2014
DOI: 10.1387/ijdb.140254js
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of Pitx2c in Xenopus trigeminal and profundal placodes

Abstract: Cranial placodes are thickenings of the embryonic head ectoderm that contribute to the paired sense organs and to the cephalic peripheral nervous system. Here we report the spatiotemporal expression pattern of transcription factor Pitx2c during Xenopus laevis cranial placode formation, focusing more specifically on key stages of trigeminal and profundal placode development. We also compare its expression to five genes that have been associated with development of these sensory placodes, namely Foxi1c, Islet1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Therefore, we investigated whether neurogenesis was altered in vgll3-depleted embryos using markers of early trigeminal placode and the postmitotic neuronal marker N-tubulin . In stage 14 embryos, vgll3 expression does not colocalize with expression of the trigeminal placode genes islet1 , neuroD , pax3 and foxi1c ( Jeong et al, 2014 ), while in stage 20 embryos, their expression domains become closer ( ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we investigated whether neurogenesis was altered in vgll3-depleted embryos using markers of early trigeminal placode and the postmitotic neuronal marker N-tubulin . In stage 14 embryos, vgll3 expression does not colocalize with expression of the trigeminal placode genes islet1 , neuroD , pax3 and foxi1c ( Jeong et al, 2014 ), while in stage 20 embryos, their expression domains become closer ( ).…”
Section: Resultsmentioning
confidence: 99%
“…1I). We compared the expression of cyp26c1 with that of pitx2c, which is expressed in a similar region of the ectoderm (Jeong et al, 2014). We found that pitx2c expression is confined to this crescent-shaped domain and temporally precedes cyp26c1 in this region that later maps to the prospective cement gland (Fig.…”
Section: Cyp26c1 Is Expressed Anteriorly and Is A Target Of Zic1mentioning
confidence: 95%
“…To understand the developmental dynamics of cyp26c1 expression, we used qRT-PCR to compare its temporal expression to that of six1, a PPR gene, and of pitx2c (Jeong et al, 2014), a transcription factor that is a putative Zic1 target (Bae et al, 2014;Jaurena et al, 2015). cyp26c1 is activated shortly after mid-blastula transition and progressively increases until stage 22, followed by a decrease in expression over time (Fig.…”
Section: Cyp26c1 Is Expressed Anteriorly and Is A Target Of Zic1mentioning
confidence: 99%
See 1 more Smart Citation